How I do it – Lung Ultrasound for Patients with COVID-19 Pulmonary Disease (2020)
Given the general utility of lung ultrasound (LUS) for the evaluation of respiratory failure in acutely ill patients, it is logical to consider its specific advantages in COVID-19 related pulmonary disease. The authors, representing the extensive experience of the North American and European COVID-19 epicenters, present an ultrasound scanning protocol and report on the common associated ultrasound findings.